Optimal Site Selection Using Geographical Information System (GIS) Based Multi-criteria Decision Analysis (MCDA): A Case Study To Concentrated Solar Power Plants (CSP) In Brazil - Chiarani, Eduardo; Antunes, Alzir Felippe Buffara; Drago, Danielle; Oening, Ana Paula; Paschoalotto, Luís Alexandre Catussi (Anuário do Instituto de Geociências, 2023)
Optimal site selection using multi-criteria decision analysis (MCDA) is an important step to support decision makers to locate places that benefit the maximum potential of technology's preconditions. As a new, emerging and renewable technology in Brazil, concentrated solar power (CSP) plays an important role in power generation mix, and it’s crucial to indicate the viability of Brazilian regions to CSP power plants. To achieve this goal, a detailed workflow of multi-criteria analysis based on geographic information system (GIS based AHP) is set in free software, in which criteria are selected from literature, acquired as geospatial data, weighted with parity matrices through online questionnaires filled by experts, processed on QGIS with weighted linear combination (WLC), and the results validated by its AHP consistency, thematic accuracy and comparative analysis with VIKOR and TOPSIS methodologies. As a product, sites are mapped according to viability indices, with higher values in most of Northeast, Central-west and Southeast regions of Brazil, showing good stability by its validation. Thereby, the workflow with free software allows the methodology to be replicated to support decision makers in locating viable and restrictive places for technologies.